The Participant Observation Method: An Avenue To Discern One’s Interest And Research Questions Abstract - Vincent, Cynthia; Tremblay-Wragg, Émilie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
This field note outlines the reflections that arose from the use of the participant observation method as an immersive process during my doctoral research fieldwork on writing retreats. The observations made during a Thèsez-vous retreat held in January 2020 resulted in findings on the process of such a retreat and on-site interactions between participants and facilitators. This process not only highlighted the merits of this method, but also elucidated my doctoral research interests and questions. This note encourages readers to apply the participant observation method in their own research to reveal their subjectivity toward their topic of study.